2005
DOI: 10.1051/0004-6361:20053257
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a penumbral connection between solar pores

Abstract: High resolution 2D-spectro-polarimetric observations have been used to analyse the magnetic field and flow topologies of a penumbral connection between two opposite polarity solar pores. A filamentary structured Evershed-like material flow from one pore to the other along the magnetic field lines has been detected. The flow channels are co-spatial with bright penumbral filaments close to the pore which feeds the flow and the clear brightness-velocity relation vanishes close to the pore which represents the sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The velocity at the heads of the filaments reaches values up to 3.3 km s −1 , interpreted here as upflows, agrees with earlier observational results (Rimmele 1995;Rimmele & Marino 2006;Hirzberger & Kneer 2001;Hirzberger et al 2005). Such upflows are also consistent with the moving flux tube model presented by Schlichenmaier et al (1998), which predicts an upflow of 4 km s −1 at the footpoints of the penumbral filaments, but equally with the interpretation of Scharmer et al (2008) that the Evershed flow is a horizontal flow component of overturning convection.…”
Section: Discussionsupporting
confidence: 92%
“…The velocity at the heads of the filaments reaches values up to 3.3 km s −1 , interpreted here as upflows, agrees with earlier observational results (Rimmele 1995;Rimmele & Marino 2006;Hirzberger & Kneer 2001;Hirzberger et al 2005). Such upflows are also consistent with the moving flux tube model presented by Schlichenmaier et al (1998), which predicts an upflow of 4 km s −1 at the footpoints of the penumbral filaments, but equally with the interpretation of Scharmer et al (2008) that the Evershed flow is a horizontal flow component of overturning convection.…”
Section: Discussionsupporting
confidence: 92%
“…Schlichenmaier et al (2005) and Ichimoto et al (2007) came to a similar conclusion (regarding the velocities) from simpler interpretations of filtergrams and spectropolarimetric data, respectively. They also reported that the horizontal fields and the flows are associated with bright filaments in the innermost penumbra (see also Hirzberger et al 2005;Jurčák et al 2007), where the dark areas most likely represent background magnetic fields. Thus, the correlation coefficients between continuum intensity and LOS velocity/inclination change sign from the inner to the outer penumbra due to the fact that RFTs predominantly show up as bright structures in the innermost penumbra, but darken toward the outer edge of the spot.…”
Section: Discussionmentioning
confidence: 93%
“…The high spatial resolution obtained with this code was important for the detection of short-period acoustic waves (Wunnenberg et al 2002) and inter-network magnetic fields (Domínguez Cerdeña et al 2003a,b), for studies of an enhanced network region observed in Hα , of the structure of polar faculae (Okunev & Kneer 2004), of small-scale solar magnetic flux concentrations (Wiehr et al 2004;Puschmann & Wiehr 2006), as well as for polarimetry of the penumbrae of sunspots (Bello González et al 2005) and of solar pores (Hirzberger et al 2005). After the first solar Adaptive Optical system (Rimmele et al 1998(Rimmele et al , 2000(Rimmele et al , 2003, the German Vacuum Tower Telescope (VTT) at the Observatorio del Teide (von der Lühe et al 2003), as well as the Swedish 1-m Solar Telescope (SST) at the Observatorio Roque de los Muchachos (Scharmer et al 2003a,b) have been equipped with AO, which provides a real-time correction of wave front distortions induced by the Earth's atmosphere.…”
Section: Introductionmentioning
confidence: 99%